Colchicine Effect of Mitosis Root Tip by Banana Kepok Yellow (Musa paradisiaca L.) Polyploid Explants - Yana, Dellya Vivi; Ernawiati, Eti; Agustrina, Rochmah; Handayani, Tundjung Tripeni (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Colchicine can inhibit spindle formation so that doubled chromosomes fail to separate during anaphase cytologically to induce mutations that produce polyploid plants. Yellow kepok banana is a triploid banana. The supply of yellow kepok bananas is hampered by conventional cultivation methods and the limited availability of quality seeds. This study aims to determine the effect of adding colchicine compound to tissue culture media on the mitotic index, chromosome number, and chromosomal abnormalities in yellow kepok bananas and the formation of polyploid plantlets. This study was included in the experimental study by conducting mitotic preparation and observing morphology after the test sample was induced by colchicine. The results of the research that has been done show that the addition of the compound colchicine to the tissue culture medium of yellow kepok banana causes a decrease in the mitotic index, an increase in the number of chromosomes, the presence of chromosomal abnormalities, the formation of polyploid plantlets, and an increase in the number of roots, but there is a reduction in root length.